Salad days [videorecording (DVD)] (Teton Gravity Research ; Distributed by Ardustry Home Entertainment, 2008)
Salad days, noun: a time of youthful indiscretion and delinquency. What really are the salad days? TGR answers with the tightest in jib style and culture. Check it: backcountry air, cliffs, rails, urban, pipe, and more. Witness skiing's new generation experience the sessions they wish would last forever. These are the happy days, the salad days as they say, when the boys are green in judgement, cold in blood.